APPLICATION OF THE VISUALIZATION, AUDITORY, KINESTHETIC (VAK) MODEL TO STUDENT LEARNING OUTCOMES IN REGIONAL CREATIVE DANCE ART MATERIALS (TOP PADE DANCE) CLASS IV AT UPTD SPF SD NEGERI SUMBER MUKTI - Oktania, Ririn; Fitri, Aida; Mislinawati, Mislinawati (Elementary Education Research, 2025)
Most students do not understand learning, especially creative dance material. Students are not taught using practical methods but are only given theories by the teacher. The dance material taught by teachers focuses more on theory and some even skip this material. This results in the role of students becoming more passive in learning and not even knowing the learning material. The formulation of the problem in this research is "How is the Visualization, Auditory, Kinesthetic (VAK) Model Applied to Student Learning Outcomes in Regional Creative Dance Material (Top Pade Creative Dance) class IV at UPTD SPF SD Negeri Sumber Mukti?". This research aims to determine "The Application of the Visualization, Auditory, Kinesthetic (VAK) Model to Student Learning Outcomes in Class IV Regional Creative Dance Material (top pade creative dance) at UPTD SPF Sumber Mukti State Elementary School". This research uses a qualitative approach and the type of research is descriptive. The subjects in this research were 23 class IV students. The data collection techniques used are observation, tests and documentation. Procedures for using the Visualization, Auditory, Kinesthetic (VAK) model, firstly delivering the material, secondly the teacher demonstrating the movements. thirdly, provide opportunities for female students to practice. Fourth, evaluation. The overall results in this study were that students showed good achievement in the audio aspect with an average score of 75.74, followed by the visual aspect with an average score of 72.70, and finally the kinesthetic aspect with an average score of 69.74.